ÖRGÜTSEL YALNIZLIK ANKETİNİN GELİŞTİRİLMESİ VE İL MAARİF MÜFETTİŞLERİNİN ÖRGÜTSEL YALNIZLIKLARININ İNCELENMESİ. - ÖZYILDIRIM, Gülnar; KAYIKÇI, Kemal (Mehmet Akif Ersoy University Journal of Education Faculty, 2019)
The aim of this study is to develop a questionnaire in order to determine organizational loneliness of educational supervisors according to their perceptions and to examine their organizational loneliness in terms of various variables. The sample of the study which is determined through cluster sampling method from probability sampling techniques included 331 supervisors for development of the questionnaire and 287 supervisors for analysis related to independent variables. The research is designed with the correlational research model in order to examine the organizational loneliness of educational supervisors related to various variables. As a result, it can be said that “Organizational Loneliness Survey” is a valid and reliable questionnaire. In addition, it has been concluded that the educational supervisors feel the highest level of organizational loneliness in “Relations with Other Units” dimension. Moreover, there are significant differences among supervisors in “Loneliness in Social Life” dimension and in overall scale in terms of age variable. In terms of graduation program variable, there is a significant difference among supervisors in “Loneliness in Social Life” dimension and in “Loneliness in Relations with Colleagues” dimension in terms of seniority as a school administrator. However, there is no significant difference among them in terms of seniority as a teacher and as a supervisor..